Thought and Choice in Chess. - Groot, Adrianus Dingeman de (Amsterdam academic archive., 2008)
Annotation What does a chessmaster think when he prepartes his next move? How are his thoughts organized? Which methods and strategies does he use by solving his problem of choice? To answer these questions, the author did an experimental study in 1938, to which famous chessmasters participated (Alekhine, Max Euwe and Flohr). This book is still usefull for everybody who studies cognition and artificial intelligence. This title can be previewed in Google Books - http://books.google.com/books?vid=ISBN9789053569986.